The Influence of Competency and Professionalism on Employee Performance Through Career Development at the Jambi District Court Class IA - Sitepu, Maria; Bukit, Pantun; Akbar, Ali (DINASTI RESEARCH, 2024)
This research is to describe the competency, professionalism, career development and performance of employees at the Jambi District Court Class IA. From the tests carried out, it was found that career development was influenced by competence and professionalism by 0.384 or if the percentage was 38.4% while the rest was influenced by other variables. Employee performance in this case is also influenced by the competency and professionalism variables of 0.608 or if expressed as a percentage, it is 60.8%. From the results of hypothesis testing, it is known that competence and professionalism have a significant and simultaneous influence on career development and employee performance at the Jambi District Court Class IA. This research concludes that employee competency, professionalism, career development and performance are in competent, high enough, good and high conditions. Apart from that, competence and professionalism have a positive and significant influence on career development in the Jambi State Court Class IA. Likewise, career development has a positive and significant influence on employee performance.